2019
DOI: 10.5812/hepatmon.85661
|View full text |Cite
|
Sign up to set email alerts
|

Persons with Intellectual Disability: A Potential Reservoir of Invasive Strains of Hepatitis B Virus

Abstract: Background: A higher prevalence of hepatitis B virus (HBV) infection has been reported in persons with intellectual disability as well as the nurses working in closed institutions compared to the general population. Objectives: In the present study, the serological and molecular markers of HBV infection in individuals with intellectual disability of closed institutions were investigated. Methods: Blood samples were derived from 400 persons with intellectual disability living in six institutions in Tehran and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…40 In this study, G145R mutation was found in only one patient, and our findings are consistent with previous studies. 41,25 Contrary to our results, another study found no G145R mutation in Ahvaz. 42 Considering that since 1993, the hepatitis vaccine has been officially included in Iran's children's vaccination program, 43 one of our patients is infected with hepatitis B despite being under 30 years of age and receiving the vaccine, which can be due to having a mutation in the "a" determinant domain and G145R mutation.…”
Section: Discussioncontrasting
confidence: 99%
“…40 In this study, G145R mutation was found in only one patient, and our findings are consistent with previous studies. 41,25 Contrary to our results, another study found no G145R mutation in Ahvaz. 42 Considering that since 1993, the hepatitis vaccine has been officially included in Iran's children's vaccination program, 43 one of our patients is infected with hepatitis B despite being under 30 years of age and receiving the vaccine, which can be due to having a mutation in the "a" determinant domain and G145R mutation.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, 3% were HBsAg positive, which indicated the higher prevalence of HBV among nurses compared to the general population, while another study reported a prevalence of 1.7-2.1% [17]. The greater risk of HBV infection had been earlier reported among nurses [12,20]. In another study on hospital nurses in Fars province, Iran, a higher risk was reported for acquiring HBV infection compared to the general population (5% were HBsAg positive, while 12% were HBcAb positive) [21].…”
Section: Discussionmentioning
confidence: 93%
“…In a study performed on nosocomial HBV infection, it has been shown that almost half of the people who are at a high risk of HBV in the health system, are not immune to it [10]. Therefore, attendees of care centers for the mentally handicapped patients are always at the risk of HBV, and to decrease this risk factor, HBV vaccination is essential [11,12].…”
Section: Original Researchmentioning
confidence: 99%